STRATEGI KOMUNIKASI FORUM KERUKUNAN UMAT BERAGAMA DALAM PEMBINAAN KERUKUNAN UMAT LINTAS AGAMA DI KABUPATEN MOJOKERTO - Pradnyaningrat, G.A.A Agustine Dwi; Sudiana, I Gusti Ngurah; Laksana Utama, Putu Kussa (Institut Hindu Dharma Denpasar, 2019)
This research is mainly discussing about the FKUB in Mojokerto Regency where many cross-religion disputes occur. Based on that fact, the problems discussed in this reserach are (1) How is the eksistence of FKUB playing a role in maintaining the cross-religion harmony in Mojokerto? (2) What is the impact given by the FKUB in maintaining the cross-religion harmony in Mojokerto? (3) What is the benefit of communication strategy developed by FKUB in maintaining the cross-religion harmony in Mojokerto?The theories used in this reasearc are (1) the theory of existence by Soren Kierkegaard, (2) the theory of structural fungsional, (3) constructivist theory. This research is using several methods which are Qualitative method with phenomenological approach. The location of this research is Mojokerto Regency while the data used is qualitative data. The data source are primary and secondary data. The technique to determine the informan is purvosive sampling.This research found that (1) The existence of FKUB in carried out dialog between the leaders of various religions create a guideline for each religion to create peace and harmony among them selves and with others. (2) The positive impact is the harmony between religion exist but the negative effect is the bad impression while making the majority as decision maker. (3) there are three benefits gained from the comunication strategy of FKUB which are the villagers become more harmonious especially those having various religions, for the local organization, its member can blend in without thinking about their differences and third for the government officers where they can do their duty without thinking about their differences. It can be said that FKUB is doing an excellent job.